Work‐based assessment: qualitative perspectives of novice nutrition and dietetics educators. Issue 5 (23rd October 2013) - Palermo, C.; Beck, E. J.; Chung, A.; Ash, S.; Capra, S.; Truby, H.; Jolly, B.
Abstract Background The assessment of competence for health professionals including nutrition and dietetics professionals in work‐based settings is challenging. The present study aimed to explore the experiences of educators involved in the assessment of nutrition and dietetics students in the practice setting and to identify barriers and enablers to effective assessment. Methods A qualitative research approach using in‐depth interviews was employed with a convenience sample of inexperienced dietitian assessors. Interviews explored assessment practices and challenges. Data were analysed using a thematic approach within a phenomenological framework. Twelve relatively inexperienced practice educators were purposefully sampled to take part in the present study. Results Three themes emerged from these data. (i) Student learning and thus assessment is hindered by a number of barriers, including workload demands and case‐mix. Some workplaces are challenged to provide appropriate learning opportunities and environment. Adequate support for placement educators from the university, managers and their peers and planning are enablers to effective assessment. (ii) The role of the assessor and their relationship with students impacts on competence assessment. (iii) There is a lack of clarity in the tasks and responsibilities of competency‐based assessment. Conclusions The present study provides perspectives on barriers and enablers to effective assessment. It highlights the importance of reflective practice and feedback in assessment practices that are synonymous with evidence from other disciplines, which can be used to better support a work‐based competency assessment of student performance.